Metal-coated resin particles and method for producing the same, conductive paste containing the metal-coated resin particles, and conductive film

By adopting the three-layer structure of metal-coated resin particles and silver particles in the conductive paste, the problem of peeling off the silver cladding layer under thermal cycle in the prior art is solved, and a conductive film with high conductivity and thermal conductivity is realized.

CN115698379BActive Publication Date: 2024-12-20MITSUBISHI MATERIALS ELECTRONICS CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180037574.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-03
Filing Date
2021-06-24
Publication Date
2024-12-20
Estimated Expiration
2041-06-24

AI Technical Summary

Technical Problem

The existing silver-clad resin particles are peeled off due to the difference in thermal expansion rates between resin particles and silver under repeated thermal cycles, resulting in reduced cracks and conductivity of the conductive film, and the adhesion of the silver-clad resin layer is needed. .

Method used

The metal-coated resin particles with a three-layer structure include a first silver layer, a tin intermediate layer and a second silver layer. The thermal stress is relieved by the tin intermediate layer, and the adhesion of the metal-coated layer to the nuclear resin particles is enhanced, and the Spherical or flat silver particles are added to the conductive paste to improve electrical conductivity and thermal conductivity.

Benefits of technology

Under thermal cycling conditions, the peeling of the metal cladding layer is reduced, the conductivity and thermal conductivity are maintained, and the stability and performance of the conductive film are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115698379B_ABST
    Figure CN115698379B_ABST
Patent Text Reader

Abstract

A metal-coated resin particle (10) comprises a spherical core resin particle (11) and a metal coating layer (12) arranged on the surface of the core resin particle (11), wherein the metal coating layer (12) is composed of a first silver layer (12a), a tin intermediate layer (12b) and a second silver layer (12c), wherein the first silver layer (12a) is formed on the surface of the core resin particle (11), and the tin intermediate layer (12b) is formed on the surface of the first silver layer (11a), and the metal coating layer (12) is selected from tin (Sn), tin oxide (SnO), and tin oxide (SnO). x O y ) and tin hydroxide (Sn x (OH) y ) is composed of one or more metallic tin and / or tin compounds selected from the group consisting of (wherein 0.1<x<4, 0.1<y<5), and the second silver layer (12c) is formed on the surface of the tin intermediate layer (12b).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to metal-coated resin particles suitable as conductive fillers contained in conductive materials and methods for producing the same. In addition, the present invention relates to conductive pastes and conductive films containing the metal-coated resin particles. In addition, the present application claims priority based on patent application No. 2020-115826 filed in Japan on July 3, 2020, and the contents thereof are incorporated herein by reference. Background Art

[0002] As a conductive material replacing lead solder or lead-free solder, conductive adhesives such as conductive pastes, conductive spacers, conductive films, and die bonding films obtained by mixing silver-coated resin particles coated with silver with resin are known. Conductive adhesives are used in materials for forming electronic components such as electrodes or electrical wiring provided in electronic devices such as solar cell panels, liquid crystal displays, and touch panels, electronic display devices, or semiconductor elements.

[0003] In the past, there has been disclosed a silver-coated spherical resin particle, characterized in that it comprises: a spherical resin particle; a tin adsorption layer provided on the surface of the spherical resin particle; and silver coated on the surface of the tin adsorption layer, wherein the amount of silver is 2 to 80 parts by mass relative to 100 parts by mass of the silver-coated spherical resin particle, and the crystallite diameter of the silver measured by X-ray diffraction method is 18 to 24 nm (for example, refer to Patent Document 1 (claim 1, claim 6, paragraphs

[0011] ,

[0013] , and

[0026] of the specification). The silver-coated spherical resin particle is produced by the following method: the method comprises a step of pre-treating the spherical resin particle with an aqueous solution of a tin compound and a step of chemically silver-plating the spherical resin particle with a reducing agent, and in the pre-treatment, the temperature of the aqueous solution of the tin compound is set to 20 to 45° C. Patent Document 1 describes the following: According to this method, silver-coated spherical resin particles that are excellent in conductivity, excellent in adhesion between the spherical resin particles and silver, and suitable for conductive fillers can be easily produced.

[0004] In the silver-coated spherical resin particles shown in Patent Document 1, a conductive paste is prepared by mixing a binder resin into the silver-coated spherical resin particles, and the conductive paste is applied between a circuit layer composed of, for example, copper and a semiconductor chip and dried and cured to form a conductive film. In this case, the conductive film allows the semiconductor chip to be stacked and bonded to the circuit layer and ensures conductivity between the circuit layer and the semiconductor chip.

[0005] Patent Document 1: International Publication No. 2012 / 023566

[0006] With regard to the silver-coated spherical resin particles shown in Patent Document 1, although the adhesion between the spherical resin particles and silver is excellent, when the conductive film is subjected to a strict thermal cycle and repeated thermal stress, due to the difference in thermal expansion coefficients between the resin particles and silver, the thermal stress cannot be fully relieved and the silver coating layer may peel off from the surface of the spherical resin particles. The peeled portion may become the starting point of cracks in the conductive film and reduce the conductivity. Therefore, a higher level of adhesion of the silver coating layer to the spherical resin particles is required. Summary of the invention

[0007] An object of the present invention is to provide a metal-coated resin particle used as a conductive filler in a conductive film, wherein the metal coating layer has excellent adhesion to the core resin particle when the conductive film is subjected to a severe thermal cycle. Another object of the present invention is to provide a conductive paste and a conductive film capable of forming a conductive film having high electrical conductivity and thermal conductivity.

[0008] A first aspect of the present invention is a metal-coated resin particle having a spherical core resin particle and a metal coating layer disposed on the surface of the core resin particle, wherein the metal-coated resin particle is characterized in that the metal coating layer is composed of a first silver layer, a tin intermediate layer, and a second silver layer, wherein the first silver layer is formed on the surface of the core resin particle, the tin intermediate layer is formed on the surface of the first silver layer, and is selected from tin (Sn), tin oxide (SnO), and the like. x O y ) and tin hydroxide (Sn x (OH) y ) is composed of one or more metallic tin and / or tin compounds selected from the group consisting of (wherein 0.1<x<4, 0.1<y<5), and the second silver layer is formed on the surface of the tin intermediate layer.

[0009] The second viewpoint of the present invention is an invention based on the first viewpoint, wherein the first silver layer has an average thickness of 10nm to 100nm, the tin intermediate layer has an average thickness of 2nm to 20nm, the second silver layer has an average thickness of 50nm to 150nm, and the average particle size of the metal-coated resin particles is 1μm to 110μm.

[0010] A third aspect of the present invention is a conductive paste comprising 70% to 90% by mass of the metal-coated resin particles of the first aspect or the second aspect and 10% to 30% by mass of a binder resin.

[0011] A fourth aspect of the present invention is a conductive paste which, when the conductive paste is set to 100 mass %, comprises 10 mass % to 80 mass % of the metal-coated resin particles of the first aspect or the second aspect, 10 mass % to 70 mass % of spherical or flat silver particles with an aspect ratio (major diameter / minor diameter) of less than 5, and 10 mass % to 30 mass % of a binder resin.

[0012] A fifth aspect of the present invention is a conductive film using the conductive paste according to the third aspect.

[0013] A sixth aspect of the present invention is a conductive film using the conductive paste according to the fourth aspect.

[0014] A seventh aspect of the present invention is a method for producing metal-coated resin particles, comprising the following steps: mixing spherical core resin particles in an aqueous solution of a tin compound and allowing tin to be adsorbed onto the surface of the core resin particles to form a tin adsorption layer; dropping a portion of an aqueous solution containing a specified amount of a silver salt and a silver complexing agent (hereinafter sometimes referred to as a silver salt, etc.) together with a reducing agent and a pH adjuster into a slurry obtained by dispersing core resin particles having a tin adsorption layer formed on the surface in water and mixing the mixture, chemically silver-plating the core resin particles in the mixed solution to replace the tin adsorption layer with a first silver layer; stirring the mixed solution and maintaining it for a specified time to form a tin intermediate layer on the surface of the first silver layer; and further dropping the remaining portion of the aqueous solution containing a specified amount of the silver salt and the silver complexing agent (silver salt, etc.) together with the reducing agent and the pH adjuster into the mixed solution and mixing the mixture, continuing to chemically silver-plating the core resin particles in the mixed solution to form a second silver layer on the surface of the tin intermediate layer.

[0015] The eighth aspect of the present invention is an invention based on the seventh aspect, which is a method for producing metal-coated resin particles, wherein, when the specified amount is set to 100 mass %, a portion of the aqueous solution containing the silver salt and the silver complexing agent is greater than 5 mass % and less than 70 mass %, and the remaining portion of the aqueous solution containing the silver salt and the silver complexing agent is greater than 30 mass % and less than 95 mass %.

[0016] The ninth aspect of the present invention is an invention based on the seventh aspect or the eighth aspect, which is a method for producing metal-coated resin particles, wherein when the spherical core resin particles are mixed with an aqueous solution of a tin compound, the temperature of the aqueous solution of the tin compound is greater than 45°C and less than 90°C.

[0017] The spherical metal-coated resin particles of the first aspect of the present invention have spherical core resin particles and a metal coating layer arranged on the surface of the core resin particles. Moreover, the metal coating layer is composed of a first silver layer formed on the surface of the core resin particles, a tin intermediate layer formed on the surface of the first silver layer, and a second silver layer formed on the surface of the tin intermediate layer. Since there is a tin intermediate layer between the first silver layer and the second silver layer, the thickness of the silver layer formed on the surface of the core resin particles is divided into two. When the metal-coated resin particles are used as conductive fillers for conductive films and the conductive films are subjected to strict thermal cycles, since the tin intermediate layer has the effect of relaxing thermal stress, the metal coating layer is difficult to peel off from the surface of the core resin particles, and the metal coating layer has excellent adhesion to the core resin particles, thereby being able to obtain a conductive film with high electrical conductivity and thermal conductivity.

[0018] For the spherical metal-coated resin particles of the second aspect of the present invention, the first silver layer, the tin intermediate layer and the second silver layer each have a specified thickness range, so that when thermal stress is repeatedly applied to the metal coating layer in a strict thermal cycle, the metal coating is more difficult to peel off from the surface of the core resin particle, and the metal coating has better adhesion to the core resin particle, thereby obtaining a conductive film with higher electrical conductivity and thermal conductivity.

[0019] The conductive paste of the third and fourth aspects of the present invention contains the metal-coated resin particles as a conductive filler, and the conductive film of the fifth and sixth aspects is formed by the conductive paste. When the conductive film is subjected to a strict thermal cycle, a conductive film whose resistance and thermal conductivity are not deteriorated can be formed compared to a conductive film containing conventional metal-coated resin particles as a conductive filler. In particular, since the conductive paste of the fourth aspect also contains spherical or flat silver particles with an aspect ratio (major diameter / minor diameter) of 5 or less as a conductive filler, the contact ratio between the metal-coated resin particles and the silver particles increases, thereby having the effect of further improving the electrical conductivity and thermal conductivity.

[0020] In the method for producing metal-coated resin particles of the seventh aspect of the present invention, first, a portion of a specified amount of silver salt, etc. is dropped into the tin adsorption layer formed on the surface of the core resin particle and mixed, thereby replacing tin with silver in the mixed solution to form a first silver layer. Then, the mixed solution is stirred and maintained for a specified time, thereby forming a tin intermediate layer on the surface of the first silver layer. Then, the remaining portion of the specified amount of silver salt, etc. is dropped into the mixed solution and mixed, thereby forming a second silver layer on the surface of the tin intermediate layer. Thus, a metal coating layer consisting of three layers of the first silver layer, the tin intermediate layer and the second silver layer is formed on the surface of the core resin particle. Here, since the tin intermediate layer divides the thickness of the silver layer into two, when the metal-coated resin particle is used as a conductive filler for a conductive film and the conductive film is subjected to a strict thermal cycle, thermal stress is relieved. As a result, the metal coating layer is difficult to peel off from the surface of the core resin particle, and metal-coated resin particles with excellent adhesion of the metal coating layer to the core resin particle can be manufactured.

[0021] In the method for producing metal-coated resin particles according to the eighth aspect of the present invention, when the prescribed amount is set to 100 mass %, a portion of the aqueous solution containing the silver salt and the silver complexing agent is greater than 5 mass % and less than 70 mass %, and the remaining portion of the aqueous solution containing the silver salt and the silver complexing agent is greater than 30 mass % and less than 95 mass %, so that the thickness of the first silver layer and the thickness of the second silver layer can be controlled within the desired range, respectively.

[0022] In the method for producing metal-coated resin particles according to the ninth aspect of the present invention, when the spherical core resin particles are mixed into an aqueous solution of a tin compound, the temperature of the aqueous solution of the tin compound is greater than 45° C. and less than 90° C., so that the amount of tin adsorbed by tin ions in the aqueous solution onto the surface of the core resin particles increases, thereby increasing the thickness of the first silver layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic cross-sectional view showing the whole of the metal-coated resin particle according to the embodiment of the present invention and a schematic cross-sectional view showing a part thereof in an enlarged manner.

[0024] Figure 2 (a) is a photograph of the metal-coated resin particles in the conductive film after the thermal cycle test of the joint body using the conductive paste obtained in Test Example 1, which was taken by a scanning electron microscope (30,000 times). Figure 2 (b) was taken using a transmission electron microscope (100,000 times) to magnify the image. Figure 2 (a) is a photograph of a portion of a first silver layer, a tin intermediate layer, and a second silver layer of a spherical metal-coated resin particle.

[0025] Figure 3This is a flowchart showing a method for producing metal-coated resin particles according to an embodiment of the present invention.

[0026] Figure 4 This is a photograph of the metal-coated resin particles in the conductive film after the thermal cycle test of the joint body using the conductive paste obtained in Comparative Test Example 1, which was taken using a scanning electron microscope (30,000 times). DETAILED DESCRIPTION

[0027] Next, a mode for carrying out the present invention will be described based on the drawings.

[0028] [Metal-coated resin particles]

[0029] First, the spherical metal-coated resin particles of this embodiment are described. Figure 1 As shown, the spherical metal-coated resin particle 10 of the present embodiment is composed of a spherical core resin particle 11 and a metal coating layer 12 coating the spherical core resin particle 11. The metal coating layer 12 is composed of a first silver layer 12a formed on the surface of the core resin particle 11, a tin intermediate layer 12b formed on the surface of the first silver layer 12a, and a second silver layer 12c formed on the surface of the tin intermediate layer 12b.

[0030] (Core resin particles)

[0031] The average particle size of the core resin particles 11 is preferably greater than 0.46 μm and less than 109.88 μm. When the average particle size is less than 0.46 μm, the surface area of ​​the resin particles becomes larger, and more silver is required to obtain the conductivity required as conductive particles. If the average particle size is greater than 109.88 μm, it is easy to make the silver-coated resin particles difficult to apply to fine patterns. For the metal-coated resin particles 10, if the average particle size of the core resin particles 11 and the thickness of the metal coating layer 12 described later are considered, the average particle size is 1 μm to 110 μm. The average particle size is a volume-based median diameter measured by a laser diffraction particle size distribution meter (manufactured by Shimadzu Corporation: SDLD200VER).

[0032] The closer the core resin particle 11 is to a sphere, the more preferred it is, but it can also be an elliptical particle or have several concave-convex shapes on the particle surface that are larger than the roughened concave shape. However, in the case of sharp protrusions, the adhesion of the plating film will be reduced during plating, and the dispersibility in the binder will be reduced when mixed with a binder as a resin, thereby causing damage to the conductivity and insulation reproduction when the metal-coated resin particles are used as isotropic conductive pastes and anisotropic conductive pastes, so it is not preferred. The core resin particle 11 is not limited to being solid, but can also be hollow. The aspect ratio as the ratio of the major diameter to the minor diameter of the resin particle is preferably in the range of 1 to 1.5, more preferably in the range of 1 to 1.3, and further preferably in the range of 1 to 1.1. The aspect ratio is a value obtained by measuring the ratio of the major diameter to the minor diameter (major diameter / minor diameter) of 10 particles by observation with a scanning electron microscope (manufactured by Hitachi HIGH TECHNOLOGIES, Ltd.: SU-1500) and averaging them.

[0033] As the core resin particles 11, for example, silicone resin particles, aromatic polyamide resin particles, fluororesin particles, polysulfone resin particles, polyether resin particles, polyimide resin particles, polyamide-imide resin particles, epoxy resin particles, phenolic resin particles, acrylic resin particles, acrylic-styrene copolymer particles, polyurethane particles, rubber particles, styrene resin particles, and resin particles having a core-shell structure can be used. Examples of silicone resin particles include polysilsesquioxane (PSQ) resin particles and polymethylsilsesquioxane (PMSQ) resin particles. Examples of aromatic polyamide resin particles include polyisophthalamide (MPIA) resin particles and polyparaphenylene terephthalamide (PPTA) resin particles. As examples of fluororesin particles, polytetrafluoroethylene (PTFE) resin particles, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride (THV) resin particles, polyvinylidene fluoride (PVDF) resin particles, polychlorotrifluoroethylene (PCTFE) resin particles, chlorotrifluoroethylene-ethylene (ECTFE) resin particles, tetrafluoroethylene-ethylene (ETFE) resin particles, tetrafluoroethylene-hexafluoropropylene (FEP) resin particles, tetrafluoroethylene-perfluoroalkyl vinyl ether (PFA) resin particles, etc. can be cited. As examples of polysulfone resin particles, polyphenylene sulfide (PPS) resin particles, polyethersulfone (PES) resin particles, etc. can be cited. As examples of polyether resin particles, polyetheretherketone (PEEK) resin particles, polyphenylene ether (PPE) resin particles, etc. can be cited. As examples of phenolic resin particles, novolac type phenolic resin particles, resol type phenolic resin particles, or phenolic resin particles obtained by modifying a part of them, etc. can be cited. Examples of polyurethane particles include polyester polyurethane particles and polyol polyurethane particles. Examples of rubber particles include silicone rubber particles and fluororubber particles. Examples of resin particles having a core-shell structure include acrylic resin core-silicone resin shell resin particles. Acrylic resin core-silicone resin shell resin particles are prepared by coating acrylic resin particles with a silicone resin film.

[0034] (Metal cladding)

[0035] It is preferred that the first silver layer 12a as the inner layer in the metal coating layer 12 has an average thickness of 10nm to 100nm, the tin intermediate layer 12b has an average thickness of 2nm to 20nm, and the second silver layer 12c as the outer layer has an average thickness of 50nm to 150nm. More preferably, the average thickness of the first silver layer 12a is 10nm to 90nm, the average thickness of the tin intermediate layer 12b is 3nm to 15nm, and the average thickness of the second silver layer 12c is 60nm to 140nm. When the average thickness of the first silver layer 12a is less than 10nm, the tin intermediate layer 12b is in direct contact with the core resin particle 11, and the characteristics of the metal-coated resin particle 11 are the same as those of the conventional metal-coated resin particle, and it is difficult to obtain the effect of the present invention. If the average thickness of the first silver layer 12a is greater than 100nm, the thickness of the metal coating layer 12 plus the thickness of the tin intermediate layer and the second silver layer becomes large, the metal coating layer 12 will be easily peeled off from the core resin particle 11, and the conductivity of the metal-coated resin particle 10 will be easily reduced.

[0036] When the average thickness of the tin intermediate layer 12b is less than 2nm, the effect of relieving the thermal stress generated by the metal coating layer 12 when the heat load is applied to the metal-coated resin particle 10 is reduced, and the characteristics are the same as those of the conventional metal-coated resin particles, and it is difficult to obtain the effect of the present invention. If the average thickness of the tin intermediate layer 12b is greater than 20nm, the thickness of the metal coating layer 12 plus the thickness of the first silver layer and the second silver layer becomes larger, and the conductivity of the metal-coated resin particle 10 is likely to be reduced. If the thickness of the metal coating layer 12 is not increased, the thickness of the first silver layer and the second silver layer becomes relatively small, and the conductivity of the metal-coated resin particle 10 is likely to be reduced. When the average thickness of the second silver layer 12c is less than 50nm, the tin intermediate layer 12b is likely to be exposed to the outside of the metal-coated resin particle 10, the powder volume resistivity of the metal-coated resin particle 10 becomes higher, and the conductivity of the metal-coated resin particle 10 is likely to be reduced. If the average thickness of the second silver layer 12 c is greater than 150 nm, the thickness of the metal coating layer 12 including the thickness of the first silver layer and the tin intermediate layer becomes large, and the metal coating layer 12 is easily peeled off from the core resin particle 11 .

[0037] The average thickness of the first silver layer 12a, the tin intermediate layer 12b, and the second silver layer 12c is obtained in the following manner. First, a FIB (focused ion beam device) is used to expose the cross section of the spherical metal-coated resin particles 10 scattered on a carbon sample table to a thickness of about 100 nm to prepare a sample. Next, a scanning electron microscope (SEM) is used for 10 metal-coated resin particles 10, and the cross-sectional shape of the interface between the metal coating layer and the core resin particle in the sample with the cross section exposed is observed multiple times in a manner that the entire metal coating layer 12 can be observed without repetition within a range of 5000 square nanometers on the surface of the core resin particle 11. The thickness of each of the first silver layer 12a, the tin intermediate layer 12b, and the second silver layer 12c is measured, and the average value of the 10 is taken as the average thickness of each layer.

[0038] The total silver coating amount (content) of the first silver layer 12a and the second silver layer 12c of the metal-coated resin particle 10 depends on the average particle size of the core resin particle 11 and the degree of the desired conductivity, and is preferably 2 to 90 parts by mass relative to 100 parts by mass of the metal-coated resin particle. If the silver content is less than 2 parts by mass relative to 100 parts by mass of the metal-coated resin particle, when the metal-coated resin particle is dispersed as a conductive particle, it may be difficult to obtain contact points between silver particles and difficult to impart sufficient conductivity. On the other hand, if the silver content is greater than 90 parts by mass, the specific gravity becomes large and the cost also becomes high, and the conductivity is easily saturated. The silver content is more preferably 28 to 85 parts by mass, and further more preferably 28 to 80 parts by mass. The ratio of the silver amount of the second silver layer 12c when the silver amount of the first silver layer 12a is set to 1 is preferably 1:2 to 5.

[0039] The tin content of the tin intermediate layer of the metal-coated resin particle 10 is the amount of tin contained in the metal tin and / or tin compound constituting the tin intermediate layer. The tin content depends on the average particle size of the core resin particle 11 and the coating amount of the tin intermediate layer, and is preferably 1 to 5 parts by mass relative to 100 parts by mass of the metal-coated resin particle.

[0040] [Method for producing metal-coated resin particles]

[0041] Next, refer to Figure 3 The method for producing the metal-coated resin particles of this embodiment is described. Figure 3 As shown, the manufacturing method is a method for obtaining metal-coated resin particles 10 through the following steps: that is, step S01 of forming a tin adsorption layer on the surface of the core resin particle 11; step S02 of forming a first silver layer by replacing the tin in the tin adsorption layer with silver; step S03 of forming a tin intermediate layer on the surface of the first silver layer; and step S04 of forming a second silver layer on the surface of the tin intermediate layer.

[0042] (Tin adsorption layer forming step)

[0043] In the tin adsorption layer forming step S01, tin, which is a metal lower than silver, is adsorbed on the surface of the core resin particle 11 to form a tin adsorption layer. Regarding the tin adsorption treatment, the core resin particles are dispersed in water in advance, and an aqueous solution of a tin compound is added to the dispersion and stirred. The core resin particles 11 may also be added to the aqueous solution of the tin compound and stirred. In the tin adsorption treatment, divalent ions of tin are adsorbed on the surface of the core resin particles 11. The core resin particles 11 adsorbed with tin are filtered and washed with water. The above stirring time is appropriately determined according to the temperature of the aqueous solution of the tin compound and the content of the tin compound as described below, and is preferably 0.5 hours to 24 hours. The temperature of the aqueous solution of the tin compound is preferably in the range of greater than 45°C and less than 90°C. More preferably, it is greater than 45°C and less than 80°C. At below 45°C, the tin ions in the aqueous solution of the tin compound are difficult to activate, and tin is difficult to adsorb on the surface of the core resin particles. The higher the temperature within the above range, the more activated the tin ions in the aqueous solution of the tin compound are, and the divalent tin ions are easily adsorbed on the surface of the core resin particles, and the unadsorbed divalent tin ions exist in the above aqueous solution. According to the tin adsorption treatment method, for the microparticles of resins such as acrylic resins, phenolic resins, and styrene resins with poor adhesion, the tin that is sufficiently adsorbed in the initial stage is replaced with silver in the chemical plating treatment described later, so that the replaced silver adheres and adheres to the resin surface. However, when the temperature of the aqueous solution of the tin compound is greater than 90°C, the aqueous solution becomes unstable due to oxidation of the tin compound, and there is a possibility that the tin in the aqueous solution of the tin compound will not be sufficiently attached to the core resin particles.

[0044] Examples of the tin compound used in the tin adsorption treatment include stannous chloride, stannous fluoride, stannous bromide, and stannous iodide. When stannous chloride is used, the content of stannous chloride in the aqueous solution of the tin compound is preferably 10 g / dm 3 ~100g / dm 3 If the content of stannous fluoride is 10g / dm 3 If the content of stannous fluoride is 100 g / dm 3 Hereinafter, it is easy to control the amount of inevitable impurities in stannous fluoride. In addition, stannous chloride can be contained in the aqueous solution of the tin compound until saturation.

[0045] The aqueous solution of the tin compound preferably contains 0.5 cm hydrochloric acid per 1 g of stannous fluoride. 3 ~2cm 3 . Hydrochloric acid is added in the form of 35 mass % hydrochloric acid. If the amount of hydrochloric acid is 0.5 cm 3 If the amount of hydrochloric acid is 2 cm 3Below this value, since the pH of the aqueous solution of the tin compound does not become too low, tin can be efficiently adsorbed to the resin particles.

[0046] (First Silver Layer Formation Step)

[0047] In the first silver layer forming step S02, the core resin particles 11 having a tin adsorption layer formed on the surface are dispersed in water to prepare a slurry, a portion of an aqueous solution (silver salt, etc.) containing a predetermined amount of silver salt and a silver complexing agent is dropped into the slurry together with a reducing agent and a pH adjusting agent and mixed, and the core resin particles are chemically silver plated in the mixed solution to replace the tin adsorption layer with the first silver layer 12a (see Figure 1 ). Here, when the above-mentioned prescribed amount is set to 100 mass %, a portion of the above-mentioned silver salt, etc. is preferably greater than 5 mass % and less than 70 mass %, and more preferably greater than 10 mass % and less than 40 mass %. The amount is determined according to the thickness of the first silver layer to be formed. In the second silver layer forming step S04 described later, the remaining portion of the above-mentioned silver salt, etc. is preferably greater than 30 mass % and less than 95 mass %, and more preferably greater than 60 mass % and less than 90 mass %. The temperature of the above-mentioned mixed solution is preferably 15°C to 30°C. When it is less than 15°C, the crystallites of the first silver layer 12a become coarse. If it is greater than 30°C, the first silver layer 12a will be easily peeled off from the core resin particle 11 because the first silver layer as a plating film grows rapidly and loses the density of the silver film.

[0048] In the first silver layer forming process, the divalent tin ions adsorbed on the surface of the core resin particle 11 by the aforementioned tin adsorption treatment become tetravalent ions and dissolve to release divalent electrons. Then, the silver ions receive electrons and precipitate in the form of metal to the part of the core resin particle 11 adsorbed with tin. Afterwards, if all the divalent tin ions become tetravalent ions and dissolve in the aqueous solution, the substitution reaction of tin and silver ends. In this substitution reaction, the catalyst is oxidized by the reducing agent to release electrons and the silver ions in the solution receive the electrons to precipitate silver. Through the above-mentioned substitution reaction and reduction reaction, the surface of the core resin particle 11 is coated with a first silver layer 12a. The adsorbed tin layer causes a substitution reaction between tin and silver in the initial stage of chemical plating. After the substitution reaction ends, silver is coated by a chemical plating reaction using a reducing agent. In the above-mentioned substitution reaction, a part of the divalent tin ions in the aqueous solution of the tin compound are replaced with silver, and the remaining divalent tin ions in the aqueous solution of the tin compound are used to form the subsequent tin intermediate layer.

[0049] As the above-mentioned silver salt, silver nitrate or a solution obtained by dissolving silver in nitric acid can be used. The silver complexing agent is preferably completely dissolved in the electrolyte. As the silver complexing agent, salts such as ammonia, ethylenediaminetetraacetic acid, tetrasodium ethylenediaminetetraacetic acid, nitrotriacetic acid, triethylenetetraaminehexaacetic acid, sodium thiosulfate, succinate, succinimide, citrate, etc. can be used. As a pH adjusting agent, an alkaline aqueous solution of sodium hydroxide, potassium hydroxide, etc. can be used. As a reducing agent, formalin, glucose, Rochelle salt (sodium potassium tartrate), hydrazine and its derivatives, hydroquinone, L-ascorbic acid or formic acid, etc. can be used. In particular, formalin as an aqueous solution of formaldehyde is preferred, more preferably a mixture of at least two or more reducing agents containing formaldehyde, and most preferably a mixture of reducing agents containing formaldehyde and glucose.

[0050] (Tin intermediate layer forming step)

[0051] In the tin intermediate layer forming step S03, the tin intermediate layer 12b is formed by depositing the free tin in the mixed solution that is not completely replaced when forming the first silver layer 12 as the remaining part on the surface of the first silver layer 12a. The amount of free tin in the mixed solution can be obtained by analysis, and the concentration of free tin can be adjusted by adding a tin compound as needed. In order to form the tin intermediate layer 12b, the mixed solution is stirred and maintained for a predetermined time. The predetermined holding time is appropriately determined according to the temperature of the mixed solution and the amount of free tin, and is preferably 0.5 hours to 1.5 hours. In addition, the longer the holding time, the greater the thickness of the tin intermediate layer 12b. On the contrary, the shorter the holding time, the smaller its thickness. The temperature of the mixed solution is preferably in the range of 10°C to 30°C. If the mixed solution is stirred and maintained, the free tin becomes a divalent ion and becomes tin hydroxide (Sn(OH)2) through the alkaline aqueous solution of the pH adjuster, and is deposited on the surface of the first silver layer 12a to form the tin intermediate layer 12b. The tin intermediate layer 12b is made of a material selected from tin (Sn), tin oxide (Sn x O y ) and tin hydroxide (Sn x (OH) y ) is composed of one or more metallic tin and / or tin compounds selected from the group consisting of ) (wherein 0.1<x<4, 0.1<y<5).

[0052] (Second Silver Layer Formation Step)

[0053] In the second silver layer forming step S04, the remaining part (silver salt, etc.) of the aqueous solution containing the above-mentioned prescribed amount of silver salt and silver complexing agent is further added dropwise to the above-mentioned mixed solution together with the same reducing agent and pH adjusting agent as used in step S02, and the reducing agent and pH adjusting agent are mixed, and the core resin particles 11 are further subjected to chemical silver plating in the mixed solution to form the second silver layer 12c on the surface of the tin intermediate layer 12b. Thus, the metal-coated resin particles 10 are obtained. As described above, when the above-mentioned prescribed amount is set to 100% by mass, the remaining part of the above-mentioned silver salt, etc. is preferably 30% by mass or more and less than 95% by mass, and more preferably 60% by mass or more and less than 90% by mass. The amount is determined according to the thickness of the second silver layer to be formed. The temperature of the above-mentioned mixed solution is preferably 10°C to 30°C. The reason for preferring this temperature range is the same as the reason described in step S02.

[0054] [use]

[0055] The metal-coated resin particles 10 of this embodiment are excellent as conductive fillers, and are particularly suitable for use as conductive fillers in conductive materials such as conductive adhesives, conductive films (sheets), conductive rubbers (elastomers), conductive adhesives, heat sinks, thermal greases, and TIMs (Thermal Interface Materials) or conductive spacers.

[0056] (Conductive adhesive)

[0057] Conductive adhesives are divided into isotropic conductive adhesives (ICA) and anisotropic conductive adhesives (ACA). In addition, the adhesive has a paste-like, film-like, and ink-like form depending on the form of the adhesive. With regard to isotropic conductive adhesives, since the adhesive shrinks when the adhesive is cured, fillers are in contact with each other in the longitudinal, transverse, and oblique directions, and thus the fillers are in contact with the conductive objects to be connected to obtain conductivity. It is also possible to form a sheet using an isotropic conductive adhesive. With regard to anisotropic conductive adhesives, fillers are dispersed in the adhesive and the anisotropic conductive adhesive is inserted between the conductive objects to be connected. By applying pressure in the longitudinal direction, the fillers between the conductive objects to be connected are in contact with the conductive objects to be connected in the longitudinal direction to obtain conductivity. On the other hand, with regard to the portion that is not pressurized, the fillers are arranged in the transverse direction via the adhesive as an insulator and do not contact each other, so conductivity is not obtained.

[0058] As a conductive adhesive, for example, anisotropic or isotropic conductive paste, anisotropic or isotropic conductive ink, etc. can be cited. A mixing machine such as a planetary mixer or a three-roll mill is used to uniformly mix metal-coated resin particles and an insulating binder resin to prepare a conductive adhesive. In the conductive adhesive, the metal-coated resin particles are uniformly dispersed in the insulating binder resin. The content of the metal-coated resin particles is not particularly limited and can be appropriately determined according to the purpose. When the conductive paste is set to 100% by mass, the case of containing 70% to 90% by mass of metal-coated resin particles and 10% to 30% by mass of binder resin respectively will obtain electrical conductivity and thermal conductivity, so it is preferred. In addition, in addition to containing the above-mentioned metal-coated resin particles as a conductive filler, the conductive paste may further contain spherical or flat silver particles with an aspect ratio (major diameter / minor diameter) of less than 5 as a conductive filler. The average particle size of the silver particles is preferably less than 10μm. In this case, from the viewpoint of further improving the electrical conductivity and thermal conductivity, it is preferred that the conductive paste, when taken as 100 mass %, contain 10 mass % to 80 mass % of metal-coated resin particles, 10 mass % to 70 mass % of silver particles and 10 mass % to 30 mass % of a binder resin.

[0059] The insulating binder resin in the conductive adhesive is not particularly limited, and examples thereof include compositions cured by heat or light, such as thermoplastic resins and curable resin compositions. Examples of thermoplastic resins include styrene-butadiene block copolymers, acrylic resins, ethylene-vinyl acetate resins, and phenoxy resins. Examples of thermosetting resin compositions include resin compositions containing silicone resins, epoxy resins, and mixtures thereof as main components.

[0060] (Conductive film (sheet))

[0061] As a conductive film, there is an anisotropic or isotropic conductive film formed into a film. The conductive film is made by the following method: first, a resin composition in which metal-coated resin particles are dispersed in an insulating binder resin is prepared, and then the resin composition is applied to the surface of a support film such as PET, thereby making a conductive film. The resin composition is prepared by uniformly mixing the metal-coated resin particles and the insulating binder resin using a mixing machine such as a planetary mixer or a three-roll mill. In the conductive film, the metal-coated resin particles are uniformly dispersed in the insulating binder resin on the support film. As the insulating binder resin in the conductive film, a resin composition containing resins such as acrylic resins, silicone resins, epoxy resins, phenoxy resins, or mixtures thereof as the main component can be cited. The content of the metal-coated resin particles in the resin composition of the conductive film is not particularly limited, and can be appropriately determined according to the purpose, preferably in the range of 0.5% to 90% by mass relative to 100% by mass of the binder resin.

[0062] (Conductive rubber (elastomer))

[0063] As a conductive rubber, there is a conductive rubber formed into a sheet or a rectangular shape, which can be used as a heat sink or a conductive connector. First, a double-axis roller is used to mix the adhesive rubber, the vulcanizing agent and the metal-coated resin particles, and then a hot press and a dryer are used to heat and pressurize for vulcanization and molding, thereby making a conductive rubber. As the adhesive rubber in the conductive rubber, nitrile rubber, acrylic rubber, styrene butadiene rubber, silicone rubber, fluororubber, etc. can be mentioned. The content of the metal-coated resin particles in the conductive rubber composition is not particularly limited, and can be appropriately determined according to the purpose, etc., preferably in the range of 0.5% to 90% by mass relative to 100% by mass of the adhesive rubber.

[0064] (Conductive adhesive)

[0065] As a conductive adhesive, there is a conductive adhesive or conductive gel formed into a thin sheet or a rectangular shape, which can be used as an electrical contact material, a heat sink and an electrode. The conductive adhesive can be made by the following method: first, an adhesive composition in which metal-coated resin particles are dispersed in an adhesive that becomes an insulating adhesive is made, and then the adhesive composition is applied to the surface of a support film such as PET, thereby making a conductive adhesive. As an adhesive in the conductive adhesive, acrylic adhesives, urethane adhesives, silicone adhesives, etc. can be cited. The content of the metal-coated resin particles in the composition of the conductive adhesive is not particularly limited, and can be appropriately determined according to the purpose, etc., preferably in the range of 0.5% to 90% by mass relative to 100% by mass of the adhesive.

[0066] (Thermal Grease)

[0067] As a heat dissipation grease, a substance obtained by mixing a non-volatile base oil and metal-coated resin particles can be used as a heat dissipation material. The heat dissipation grease is prepared by uniformly mixing the base oil and the metal-coated resin particles using a mixer such as a planetary mixer or a three-roll mill. Examples of the base oil used for the heat dissipation grease include silicone oil base oils, mineral oil base oils, synthetic hydrocarbon base oils, ester base oils, ether base oils, and ethylene glycol base oils or combinations thereof. The content of the metal-coated resin particles in the composition of the heat dissipation grease is not particularly limited and can be appropriately determined according to the purpose, etc. It is preferably in the range of 0.5% to 90% by mass relative to 100% by mass of the base oil.

[0068] (Conductive spacer)

[0069] For the conductive spacer, in the liquid crystal display device, the wiring parts of the upper and lower substrates that clamp the liquid crystal material are electrically connected up and down, and the gap between the substrates is kept at a specified size. The conductive spacer can be made by the following method: First, after adding metal-coated resin particles to an insulating adhesive resin such as a thermosetting resin or an ultraviolet curing adhesive, a mixing machine such as a planetary mixer or a three-roll mill is used to uniformly mix the metal-coated resin particles and the adhesive resin to prepare a resin composition, and then, the above-mentioned resin composition is applied to any one or two parts of the wiring parts of the upper and lower substrates to bond the two substrates, thereby making a conductive spacer. The content of the metal-coated resin particles is not particularly limited, and can be appropriately determined according to the purpose, etc., preferably in the range of 2% to 10% by mass relative to 100% by mass of the adhesive resin.

[0070] Example

[0071] Next, examples of the present invention will be described in detail together with comparative examples.

[0072] <Example 1>

[0073] A tin chloride aqueous solution (SnCl2 aqueous solution) is prepared for tin adsorption treatment. The tin chloride aqueous solution is prepared by using a volume of 1 dm 3 Use a measuring flask to mix 15g of stannous chloride and 15cm of hydrochloric acid with water. 3 Dilute (fix volume) to 1dm 3 The tin chloride aqueous solution was stored at a liquid temperature of 27°C. Hydrochloric acid with a concentration of 35% by mass was used. In addition, 33 g of silver nitrate (silver salt), 53 cm 3 25 mass% ammonia water, 175cm 3 of water to prepare 256 g of an aqueous silver ammonia complex solution (silver salt, etc.) containing silver nitrate.

[0074] As core resin particles, an acrylic resin (PMMA cross-linked beads) having an average particle size of 3 μm is prepared. A dispersion is prepared by dispersing 9 g of the core resin particles in water, and the above-mentioned tin chloride aqueous solution is added to the dispersion, adjusted to a temperature of 60°C and stirred at the temperature for 5 hours (tin adsorption layer forming step). Thereafter, the core resin particles are filtered and washed with water. Next, a slurry having a liquid temperature of 15°C is prepared by dispersing the core resin particles in water again, and while stirring the slurry, 85 g of a reducing agent (35% formaldehyde aqueous solution), a pH adjusting agent (sodium hydroxide aqueous solution) and a silver salt (silver ammonia complex aqueous solution) are sequentially added dropwise to the slurry to prepare a mixed solution. When the initially produced silver salt (a specified amount of silver salt) is set to 100% by mass, the amount of the silver salt added is 33.3% by mass (first silver layer forming step). After the above-mentioned addition, the above-mentioned mixed solution having a liquid temperature of 20°C is stirred for 1 hour and maintained (tin intermediate layer forming step). Next, while stirring the mixed solution at a liquid temperature of 20° C., 66.7% by mass of the remaining portion of the silver salt, etc. (silver-ammine complex aqueous solution) when the initially prepared predetermined amount of the silver salt, etc. is set to 100% by mass is added dropwise to the mixed solution (second silver layer forming step). Thus, metal-coated resin particles having a metal coating layer are obtained in which the core resin particles have a metal coating layer. The cross section of the metal-coated resin particles was observed using a scanning electron microscope, and the result was a three-layer structure. The composition analysis was performed using EDX (energy dispersive X-ray analysis), and the results showed that the first layer and the third layer were Ag, respectively, and the second layer of the intermediate layer was Sn and O (oxygen).

[0075] Table 1 below shows (1) the amount, temperature, and stirring time of the SnCl2 aqueous solution in the tin adsorption layer forming step, (2) the amount of a predetermined amount of silver salt or the like (silver ammonia complex aqueous solution), (3) the temperature, dropping time, and ratio of the dropping amount of the silver salt or the like to the predetermined amount of the silver salt or the like in the first silver layer forming step, (4) the temperature and holding time of the mixed solution in the tin intermediate layer forming step, and (5) the temperature, dropping time, and ratio of the dropping amount of the silver salt or the like to the predetermined amount of the silver salt or the like in the second silver layer forming step.

[0076] [Table 1]

[0077]

[0078] <Examples 2 to 10>

[0079] In Examples 2 to 10, in order to change the thickness of each of the first silver layer, the tin intermediate layer, and the second silver layer, the production conditions of each step were changed as shown in Table 1 to produce metal-coated resin particles.

[0080] <Comparative Example 1>

[0081] An example in which the tin intermediate layer was not formed by continuously dropping the entire amount of the silver salt or the like (silver ammine complex aqueous solution) at once is referred to as Comparative Example 1.

[0082] The types and average particle sizes of the core resin particles used as the raw materials of the metal-coated resin particles obtained in Examples 1 to 10 and Comparative Example 1, the average thickness of each layer constituting the metal coating layer of the metal-coated resin particles, and the average particle size of the metal-coated resin particles are shown in Table 2 below. The average thickness of each layer and the average particle size of the particles were measured by the above-mentioned method.

[0083] [Table 2]

[0084]

[0085] <Test Example 1>

[0086] In Test Example 1, 80% by mass of the metal-coated resin particles of Example 1 as a conductive filler and 20% by mass of a multifunctional epoxy resin (ADEKA Resin EP-3950S, manufactured by ADEKA Corporation) as a binder resin were mixed to prepare a conductive paste. The composition of the conductive paste (type and ratio of metal-coated resin particles, average particle size, shape and ratio of silver particles, type and ratio of binder resin) is shown in Table 3 below.

[0087] [Table 3]

[0088]

[0089] <Test Examples 2 to 13>

[0090] As shown in Table 3, conductive pastes of Test Examples 2 to 13 were prepared by making the content of each metal-coated resin particle of Examples 2 to 10 the same as or changing the content of Test Example 1. Test Examples 6, 8 to 11 show examples containing metal-coated resin particles and silver particles.

[0091] <Comparative Test Example 1>

[0092] As shown in Table 3 above, the conductive paste of Comparative Test Example 1 was prepared using the metal-coated resin particles of Comparative Example 1 alone.

[0093] <Comparative test and evaluation>

[0094] A joint body was prepared using the 14 kinds of conductive pastes obtained in Test Examples 1 to 13 and Comparative Test Example 1, and a thermal cycle test was performed on the joint body. In addition, a molded body was prepared from the conductive paste and thermally cured, and the thermal conductivity of the cured body was measured.

[0095] (i) Hot and cold cycle test

[0096] Use the conductive pastes obtained in Test Examples 1 to 13 and Comparative Test Example 1 to make joint bodies, respectively, and perform hot and cold cycle tests on these joint bodies. Specifically, first, apply each conductive paste in a pattern with a length, width and thickness of 2 mm, 2 mm and 30 μm, respectively, on a square copper plate with a length and width of 20 mm and 20 mm, respectively, to form a coating film. Then, place a square silicon chip with a length and width of 2 mm and 2 mm, respectively, on the coating film. Then, put it into an electric furnace and keep it at a temperature of 180°C for 30 minutes to solidify the coating film and form a conductive film, thereby using the conductive film to bond the silicon chip to the copper plate to make joint bodies. Then, perform hot and cold cycle tests on these joint bodies. The thermal shock test was performed using a thermal shock tester (TSB-51 manufactured by ESPEC Corporation), and the bonded body was kept at -20°C for 5 minutes in a liquid phase (Fluorinert FC-43 manufactured by 3M Corporation), and then kept at 150°C for 5 minutes for 500 times. Next, the bonding rates of the bonded body before and after the thermal shock test were measured.

[0097] The bonding rate of the bonded product is evaluated as follows: First, the bonding rate (%) of the interface between the copper plate and the silicon chip is evaluated using an ultrasonic flaw detector, and the bonding rate (%) is calculated according to the following formula (1).

[0098] Bonding rate = (initial bonding area - peeling area) / initial bonding area × 100 (1)

[0099] Here, the initial bonding area refers to the area to be bonded before bonding, that is, the area of ​​the silicon chip. Since the peeling is represented by the white part in the bonding part in the ultrasonic flaw detection image, the area of ​​the white part is the peeling area. In addition, when a crack occurs inside the bonding layer or at the bonding interface between the copper plate and the silicon chip, the crack is represented by the white part in the ultrasonic flaw detection image, so the crack is also evaluated as the peeling area. The results are shown in Table 3 above.

[0100] Figure 2 (a) shows a photograph of metal-coated resin particles in a conductive film after a hot-cold cycle test of a joint body using the conductive paste obtained in Test Example 1, taken with a scanning electron microscope (manufactured by Hitachi High-Technologies Corporation, model name: SU-1500) at 30,000 times magnification. Figure 2 (b) shows a transmission electron microscope (manufactured by JEOL Ltd., model name: JEM-2-1-F) at 100,000 times magnification and photographed. Figure 2A photograph of a portion of the first silver layer, the tin intermediate layer, and the second silver layer of a spherical metal-coated resin particle shown in (a) of FIG. Figure 2 The reference numerals shown in (b) are the same as Figure 1 The reference numerals shown correspond.

[0101] in addition, Figure 4 The following is a photograph of the metal-coated resin particles in the conductive film after the hot-cold cycle test of the joint body using the conductive paste obtained in Comparative Test Example 1, taken with a scanning electron microscope (manufactured by Hitachi High-Technologies Corporation, model name: SU-1500) at 30,000 times magnification. Figure 4 In the figure, reference numeral 1 is a core resin particle, reference numeral 2 is a metal coating layer, reference numeral 3 is a gap, and reference numeral 5 is a metal-coated resin particle.

[0102] Although in Figure 4 In the metal-coated resin particle 5 shown, the metal coating layer 2 is peeled off from the surface of the core resin particle 1 to form a gap 3, but Figure 2 (a) and Figure 2 In the metal-coated resin particle 10 shown in (b), the metal coating layer 12 is not peeled off from the surface of the core resin particle 11 .

[0103] (ii) Thermal conductivity

[0104] The conductive pastes obtained in Test Examples 1 to 13 and Comparative Test Example 1 were used to prepare molded bodies with a diameter of 10 mm and a thickness of 1 mm, and the molded bodies were cured at 200° C. for 20 minutes to prepare test samples. The thermal diffusivity of the obtained samples was measured by a laser flash method (TC-7000 manufactured by ULVAC Co., Ltd.), and the thermal conductivity (W / m·K) was calculated from the specific heat and density. The results are shown in Table 3 above.

[0105] As shown in Table 3, the metal-coated resin particles of Comparative Example 1, which were prepared by a conventional method of continuously dropping all the silver salts (silver-ammine complex aqueous solution) at once without forming a tin intermediate layer, were used in the conductive paste of Comparative Example 1. Therefore, the bonding rate of the bonded body after the thermal cycle test was low, which was 60%. In addition, it was found that the thermal conductivity of the sample prepared using the conductive paste was low, which was 3 W / m·K, and the thermal conductivity was not good.

[0106] In contrast, in Test Examples 12 and 13, which satisfy the features of the first aspect of the present invention and use metal-coated resin particles having a tin intermediate layer to make conductive pastes that do not satisfy the features of the second aspect of the present invention, the bonding rates of the bonded bodies after the thermal cycle test were 75% and 77%, respectively, which are higher than the bonding rate of 60% in Comparative Test Example 1. In addition, the thermal conductivities of Test Examples 12 and 13, which are samples made using these conductive pastes, are 5 W / m·K and 6 W / m·K, respectively, which are higher than the thermal conductivity of Comparative Test Example 1 of 3 W / m·K.

[0107] In Test Examples 1 to 11 that satisfy the characteristics of the second aspect of the present invention, the bonding rate of the bonded body after the thermal cycle test was 80% to 100%, which is higher than that of Test Examples 12 and 13. In addition, the thermal conductivity of the samples made using the conductive paste of Test Examples 1 to 11 was 6 W / m·K to 15 W / m·K, which is higher than that of Test Examples 12 and 13.

[0108] Industrial Applicability

[0109] The spherical metal-coated resin particles of the present invention can be used as a conductive filler as a conductive binder for a conductive material forming electronic components such as electrodes or electrical wiring provided in electronic devices such as solar cell panels, liquid crystal displays, touch panels, electronic display devices, or semiconductor elements.

Claims

1. A metal-coated resin particle comprising a spherical core resin particle and a metal coating layer disposed on the surface of the core resin particle, wherein the metal-coated resin particle is characterized in that: The metal coating layer is composed of a first silver layer, a tin intermediate layer and a second silver layer, wherein the first silver layer is formed on the surface of the core resin particle, the tin intermediate layer is formed on the surface of the first silver layer, and is selected from tin (Sn), tin oxide (SnO x O y ) and tin hydroxide (Sn x (OH) y ) is composed of one or more metallic tin and / or tin compounds selected from the group consisting of: 0.1<x<4, 0.1<y<5, the second silver layer is formed on the surface of the tin intermediate layer.

2. The metal-coated resin particle according to claim 1, wherein The first silver layer has an average thickness of 10 nm to 100 nm, the tin intermediate layer has an average thickness of 2 nm to 20 nm, the second silver layer has an average thickness of 50 nm to 150 nm, and the average particle size of the metal-coated resin particles is 1 μm to 110 μm.

3. A conductive paste comprising 70 to 90% by mass of the metal-coated resin particles according to claim 1 or 2 and 10 to 30% by mass of a binder resin.

4. A conductive paste, comprising 10% to 80% by mass of the metal-coated resin particles according to claim 1 or 2, 10% to 70% by mass of spherical or flat silver particles having an aspect ratio of 5 or less, and 10% to 30% by mass of a binder resin, when the conductive paste is taken as 100% by mass, wherein: The aspect ratio is the ratio of the major diameter to the minor diameter.

5. A conductive film using the conductive paste according to claim 3.

6. A conductive film using the conductive paste according to claim 4.

7. A method for producing metal-coated resin particles, comprising the following steps: mixing spherical core resin particles in an aqueous solution of a tin compound and allowing tin to be adsorbed onto the surface of the core resin particles to form a tin adsorption layer; adding a portion of an aqueous solution containing a predetermined amount of silver salt and a silver complexing agent together with a reducing agent and a pH adjusting agent to a slurry obtained by dispersing core resin particles having a tin adsorption layer formed on the surface in water and mixing the mixture, and chemically silver-plating the core resin particles in the mixed solution to replace the tin adsorption layer with a first silver layer; Stirring the mixed solution for a predetermined time to form a tin intermediate layer on the surface of the first silver layer; and The remaining portion of the aqueous solution containing a specified amount of the silver salt and the silver complexing agent is further added dropwise to the mixed solution together with the reducing agent and the pH adjuster and mixed, and the core resin particles are further chemically silver-plated in the mixed solution to form a second silver layer on the surface of the tin intermediate layer.

8. The method for producing metal-coated resin particles according to claim 7, wherein: When the specified amount is set to 100 mass%, a portion of the aqueous solution containing the silver salt and the silver complexing agent is greater than 5 mass% and less than 70 mass%, and the remaining portion of the aqueous solution containing the silver salt and the silver complexing agent is greater than 30 mass% and less than 95 mass%.

9. The method for producing metal-coated resin particles according to claim 8, wherein When the spherical core resin particles are mixed with an aqueous solution of a tin compound, the temperature of the aqueous solution of the tin compound is higher than 45° C. and lower than 90° C.